Epistemically Suspect Beliefs About COVID‐19: Results From a Population Survey in Finland - Kaakinen, Johanna K.; Moazami Goodarzi, Ali; Häikiö, Tuomo; Kivioja, Pasi; Mäki, Karl O.; Pritup, Daria (Wiley, 2026)
We examined the familiarity and popularity of epistemically suspect COVID-19 claims and their associations with cognitive, social and demographic factors in a sample of people living in  Finland (N = 1,077) during the pandemic (September 2021-January 2022). Endorsement of these claims was associated with pseudoscientific beliefs, less actively open-minded thinking, and preference for anecdotal information. Among social factors, lower trust in governmental institutions, science, and scientists, and reliance on alternative media, were linked to higher endorsement. Regarding demographic variables, higher education was associated with lower endorsement, though this effect was fully mediated by cognitive and social factors. Men endorsed epistemically suspect COVID-19 claims more than women, and endorsement decreased with age. These findings highlight the importance of education in fostering critical thinking skills and trust in institutions and science to effectively combat health-related misinformation.